2019
DOI: 10.5114/aoms.2017.66160
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress markers in patients with hereditary angioedema

Abstract: A b s t r a c t Introduction: Hereditary angioedema due to C1-INH deficiency (C1-INH-HAE)or with normal C1-INH is characterized by recurrent swellings due to uncontrolled production of vasoactive mediators, among which bradykinin (BK) is crucial. Through the binding and activation of the two human BK-receptors, kinins may have dual beneficial and deleterious effects in vascular and inflammation physiopathology by inducing oxidative stress. We aimed to assess the serum concentrations of advanced glycation end p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 50 publications
4
8
0
Order By: Relevance
“…24,25,[35][36][37][38][39] Our results concerning oxidative stress in C1--INH -HAE as well as the effect of bradykinin on oxidative stress in PBMCs in this patient population were presented as preliminary findings during 2018 Bradykinin Symposium in Berlin. 40 They are generally consistent with the recent study by Del Giacco et al, 18 who indicated Our results concerning the effect of exogenous bradykinin on basal and H 2 O 2 -induced ROS levels in PBMCs in patients with C1 -INH -HAE showed that bradykinin exerted a significant antioxidant effect in this group of patients. The lack of antioxidant bradykinin action in healthy controls may be associated with normal C1 -INH levels or may indicate that this effect manifests only in the case of increased oxidative stress.…”
Section: What's New?supporting
confidence: 92%
See 4 more Smart Citations
“…24,25,[35][36][37][38][39] Our results concerning oxidative stress in C1--INH -HAE as well as the effect of bradykinin on oxidative stress in PBMCs in this patient population were presented as preliminary findings during 2018 Bradykinin Symposium in Berlin. 40 They are generally consistent with the recent study by Del Giacco et al, 18 who indicated Our results concerning the effect of exogenous bradykinin on basal and H 2 O 2 -induced ROS levels in PBMCs in patients with C1 -INH -HAE showed that bradykinin exerted a significant antioxidant effect in this group of patients. The lack of antioxidant bradykinin action in healthy controls may be associated with normal C1 -INH levels or may indicate that this effect manifests only in the case of increased oxidative stress.…”
Section: What's New?supporting
confidence: 92%
“…At the same time, bradykinin was proved to stimulate the activity of the antioxidant enzymes superoxide dismutase and catalase in endothelial cells. 18,49 This recent evidence corroborates a previous study reporting an increase in superoxide dismutase, catalase, and glutathione peroxidase activity in hyperglycemic rats. 47,48 On the basis of these findings as well as our data, a hypothesis may be proposed that one of the various bradykinin effects is to maintain the redox balance.…”
Section: What's New?supporting
confidence: 90%
See 3 more Smart Citations